Prevalence and pattern of mental disorders in the state of West Bengal: Findings from the National Mental Health Survey of India 2016 - Sukanto Sarkar; Aniruddha Basu; Sucharita Mandal; Pavithra Jayashankar; Pradeep K. Saha; Raghunath Misra; Debasish Sinha; Rajarshi Neogi; Soumyadeep Saha; Vivek Benegal; Girish N. Rao; Mathew Varghese; et al. (Indian Journal of Psychiatry)
Background: West Bengal, situated in eastern India, comprising 19 districts as of 2016 and consisting of 9.13 crore population, had been one of the participating states in the National Mental Health Survey, 2015–16. Aim: To estimate the prevalence and pattern of mental disorders in a representative population in West Bengal. Materials and Methods: Based upon a multi-stage stratified random cluster sampling with probability proportionate to each stage, 2646 eligible individuals were interviewed. Standard validated instruments in Bengali like socio-demographic profiles and Mini International Neuropsychiatric Interview (MINI) version 6 were used by trained data collectors with quality monitoring as per a standardized protocol. Results: The current prevalence of mental illness in the state of West Bengal is 13.07% (12.9–13.24 95% CI), which is more than the current national average of 10.56% (10.51–10.61 95% CI). The prevalence of severe mental illness of 2.32% and suicide risk of 1.75% (1.68–1.81 95% CI) is higher than the national average. The common mental illness prevalence is 11.29 (11.13–11.45 95% CI), which is similar to the national weighted average. In West Bengal, severe mental illness is more concentrated in the rural areas in contrast to the national trend. Also, the prevalence of alcohol use disorder is 3.04 (2.96–3.13 95% CI) and epilepsy is 0.03 (0.27–0.29 95% CI), which is less than the national average. Conclusion: The prevalence of mental disorders in the state of West Bengal is higher than the national average, and for severe mental illness, the prevalence is the highest as compared to the national average.